Peripheral vision field fatigue during simulated driving : the effects of time on task and time of day on selected psychophysiological, performance and subjective responses - Robertson, Jade Kelly (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2012)
Worldwide, motor accidents are responsible for a large number of deaths and disabilities (Connor et al., 2001), and one of the major causes of motor accidents is driver fatigue. Although majority of drivers are aware of the dangers of fatigued driving, accidents related to this continues to contribute to a large percentage of all accidents, between 5 and 50% (Nilsson et al., 1997; Williamson et al., 2011). The purpose of the research was to establish the effect that fatigue renders on an individual's peripheral visual field and to determine whether a decrement in driving performance occurs at the same rate as a decrement in peripheral visual performance. Fatigue was induced through time of day as well as time on task. Sixteen students from Rhodes University were recruited, subject to no previous sleep disorders, among other criteria. Each participant was required to partake in two conditions, namely a day condition (09h00"“11h00) and a night condition (23h00"“ 01h00). Each condition consisted of a 90 minute dual task; the primary task was a tracking task, in which participants were instructed to track a white line as accurately as possible. A secondary peripheral response task was introduced, in which participants were instructed to respond as quickly as possible to the peripheral stimuli, by pressing one of two clickers located on the steering wheel. The peripheral stimuli were located at 20Âº, 30Âº and 40Âº visual angle. Psychophysiological, performance and subjective measures were obtained before, during and after the main task. The pre- and post-tests included core body temperature, critical flicker fusion frequency threshold, a digit span memory test, Wits Sleepiness Scale and a NASA-TLX questionnaire. The psychophysiological and performance measures of heart rate, heart rate variability, blink frequency, blink duration, lane deviation, number of saccades towards peripheral stimuli, response time to peripheral stimuli and the percentage of missed peripheral responses were all recorded throughout the 90 minute main dual task. The results revealed significant differences (p<0.05) for heart rate variability, number of saccades towards peripheral stimuli and the Wits Sleepiness Scale, with regard to time of day. For time on task, significant effects were established for lane deviation, response time to peripheral stimuli, percentage of missed peripheral responses, heart rate, heart rate variability, blink frequency, blink duration, critical flicker fusion frequency threshold, core body temperature and the Wits Sleepiness Scale. Eccentricity was analysed and found to be significant for response time to peripheral stimuli, as well as for the percentage of missed peripheral responses; there was a significant increase in both measures with an increase in the stimuli eccentricity. No significances were established for time of day or between the pre- and post-tests conducted for the digit span memory performance; however, a significant interactional effect between the two was established. When assessing the percentage rate of decrement of driving performance compared to the percentage rate in the decrement of the missed peripheral responses, it was found that the percentage rate of decrement was equal for both measures. Thus from this research it can be seen that, concurrent with a decrement in driving performance, there are adverse effects on an individuals' peripheral vision, which have great implications for the safety of workers in industry and transport, as well as motorists. It was also established that time on task is possibly a more appropriate variable to consider than time of day, when implementing work schedules and rest breaks in industry, transport and fields alike, as more significant findings were seen for time on task compared to time of day.,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Automobile driving simulators; Automobile driving -- Psychological aspects; Automobile driving -- Physiological aspects; Traffic accidents; Traffic safety; Fatigue; Peripheral vision